KEKUATAN DAN KELEMAHAN SUMBER DAYA MANUSIA (GURU) DALAM IMPLEMENTASI PEMBELAJARAN MENDALAM DI SD NEGERI 005 SANGASANGA - Arie Ekayudhistira; Syifa Hanum Budiawati; Winaryati; Syalma Faradila Nur; Friska Umi Puspita Sari; Widyatmike Gede Mulawarman; Akhmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the strengths and weaknesses of human resources (teachers) in implementing deep learning at SD Negeri 005 Sangasanga. Deep learning is a key component of the Merdeka Curriculum, emphasizing the development of critical thinking, creativity, and collaboration skills. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal that teachers possess several strengths that support the implementation of deep learning, including strong commitment to curriculum change, high motivation, extensive teaching experience, adequate basic pedagogical skills, and openness to new instructional approaches. However, the study also identifies several significant weaknesses, such as limited digital literacy, difficulties in designing inquiry- and project-based learning, insufficient application of authentic assessment, limited creativity in developing exploratory learning activities, and heavy administrative workloads. The conceptual model of findings indicates that the success of deep learning implementation is shaped by the interaction between teachers’ strengths and weaknesses. These results highlight the need for more targeted professional development programs and stronger institutional support to ensure the effective and sustainable implementation of deep learning practices.